Concurrent radiotherapy with palbociclib or ribociclib for metastatic breast cancer patients: Preliminary assessment of toxicity. (August 2019) - Ippolito, Edy; Greco, Carlo; Silipigni, Sonia; Dell'Aquila, Emanuela; Petrianni, Gian Marco; Tonini, Giuseppe; Fiore, Michele; D'Angelillo, Rolando Maria; Ramella, Sara
Abstract: Objective: To evaluate the early toxicity of concurrent use of radiotherapy in association with CDK4/6 inhibitors (palbociclib or ribociclib) in patients with hormone-receptors positive metastatic breast cancer. Material and methods: Records of patients with histologically proven metastatic or locally advanced breast cancer treated in our institution were reviewed. Patients who received radiotherapy and concurrent palbociclib or ribociclib were selected. Toxicity was assessed according to the National Cancer Institute Common Terminology Criteria for Adverse Events version 4.0 (NCI-CTCAE V4.0). Results: Sixteen consecutive metastatic breast cancer patients with 24 radiotherapy treatments were studied. Thirteen patients (81.3%) received palbociclib, 3 (18.7%) patients received ribociclib concurrently with RT (18 and 5 radiotherapy courses respectively). The majority of patients (68.7%) received palliative radiotherapy to the bones (median dose 30 Gy, range 8–36 Gy). Five patients (31.2%) were treated in oligo-metastatic or oligo-progressive sites of disease with higher doses (median dose = 50 Gy, range 39.6–60 Gy). The most common toxicity observed was hematological toxicity. Neutropenia was common (grade 2 = 12.5%; grade 3 = 25%, grade 4 = 6.3%); 60% of patients experiencing grade ≥ 3 neutropenia had already experienced neutropenia during previous cycles of palbociclib. One patient (6.3%) completed the RT course earlier (48 Gy of 50 Gy prescribed) and another patient (6.3%) suspended RT for 2 days. Conclusion: concomitant treatment of CDK4/6 and radiotherapy seems well tolerated; high grade hematological toxicity is common, but did not change treatment course in the majority of patients. Previous toxicity should be carefully evaluated as it usually reoccurs. Highlights: The concomitant treatment of CDK4/6 and radiotherapy is feasible. Hematological toxicity is common. High conformal radiotherapy treatment should be used to spare nearby healthy tissue. Previous CDK4/6 related toxicity should be carefully evaluated.